Burying their loved: The catholic rituals of death in Florianópolis in contemporary - Isaia, Artur Cesar (2014)
It seeks to analyze this article diversified Catholic rituals of death in the city of Florianópolis (SC), during the twentieth century, through various sources, such as written, oral and imagery. Stand out in this way, the different forms of Catholic celebrations of death among “florianopolitanos” transmitted from generation to generation as Masses performed in intention to the dead, funeral processions, wakes, funerals and Memorial Day, in the course of twentieth century.